Place-based inequalities in Portugal: a new way of looking to territories through official statistics - Mauritti, R; Botelho, M.C.; Nunes, N.; Silva, S. F. (10th European Conference on Quality in Official Statistics (Q2022), 2022)
The COVID-19 pandemic has exposed the complex relationships between the global, national, regional and local levels of the European social space, revealing the systemic and cumulative effects of different mechanisms of inequality on people's living conditions and well-being. In this context, the availability of reliable and timely social statistics assumes an increasing centrality for scientifically supported policy action. In the global-digital society, the mega-production of data, its open dissemination and often vulnerability to misinformation, require up-to-date official statistics for robust decision-making processes acting on collective challenges. Reversing long-standing trends of increasing inequality is one of those main challenges in our time. Inequality is at the heart of other major challenges such as climate change, global health, the digital transition and the future of work, inclusive participation and consolidation of democratic systems, all of which impact local spaces and the people who live there. In order to understand the causes and consequences of inequality, and to put in place effective political-institutional mechanisms for their reduction, it is essential to have a multidimensional, integrated, and multi-scaling system of indicators. As a contribution to this perspective, we present a new look at territories considering their systemic, structural, institutional and interactive relations, which manifest a set of multiple inequalities in a relevant way. Based on official statistics from mainland Portugal, we developed a quantitative multivariate analysis, namely hierarchical and non-hierarchical cluster analysis, comparing its 272 municipalities. This place-based approach was supported by 12 inequality indicators from INE (Statistics Portugal), potentially replicable to other European countries. Official statistics were used at the national, regional and municipal levels. Data from Census 2001 and 2011 and regional and municipal statistics from 2016 were used as a reference, as also data from the Personal Income Tax (IRS) from 2016. In Southern Europe and in the European context, Portugal is one of the most unequal countries. Portuguese society is crossed by five territorial configurations of inequalities, forming common features and distinctions between municipalities and regions. These territories of inequality result from complex intersections between social class, income, education, demographic density and age structure. The country is formed by «Industrial Territories in Transition», «Intermediate Territories», «Urban Networked Territories», «Innovative Territories» and «Low-Density Territories». Such territorial configurations reveal the intertwined interpenetration between social inequalities and the main dynamics that today runs through contemporary societies. European Union would benefit by considering these territorial inequalities for achieving social cohesion.